System For Penetrative Emergency Communication System - S. R. Sowmiya,; C. Saranraj,; V. Vinoth,; P. Manikandan,; S. Sadamhussian, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The use and growth of these rapidly expanding devices led to the development of Wi-Fi, which offers a technology known as Li-Fi. Utilizing LED light, Li-Fi technology allows for data transmission that is significantly more flexible and quick than Wi-Fi technology. Since light can travel almost everywhere, communication may likewise freely follow light. One area of the rapidly developing field of optical wireless communication is light fidelity. Using visible light as a medium for transmission, Li-Fi enables wireless communication within buildings. It is not possible for Wi-Fi to reach the bit rate that Li-Fi can. Li-Fi is the process of transferring data Li-Fi is an emerging technology that can function as a stand-in for a number of other emerging and established technologies. This technology is highly useful and implementable in numerous domains that are not possible with Wi-Fi and other technologies because light serves as the primary source of transmission. As a result, future Li-Fi applications can be anticipated and expanded to a variety of platforms, including the domains of education, medicine, industry, and many more.
Keywords: Li-Fi; Wi-Fi; high-brightness LED; Photodiode; Wireless Communication